2020
DOI: 10.21037/tlcr-20-189
|View full text |Cite
|
Sign up to set email alerts
|

Future perspectives from lung cancer pre-clinical models: new treatments are coming?

Abstract: Towards the sunset of the traditional biopsy era: the future is liquidThe development of personalized medicine for cancer patients relies on the unambiguous identification of the molecular drivers of their disease (1,2). Currently, tumor biopsy samples are the major source of material for biomarker measurement in order to predict response to therapy (3). This approach is biased by at least three different aspects. First, since tumor tissue is unavailable or insufficient for genetic analysis at the time of prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 137 publications
(147 reference statements)
0
10
0
Order By: Relevance
“…Overall, there was no identification of statistical differences for the clinical stage at the lung cancer group, and it is worth mentioning that over 70% of subjects were metastatic at diagnosis [ 29 ]. The results presented by Lou et al [ 30 ] also demonstrated no change in clinical stage at diagnosis for patients with lung cancer besides a shorter time-to-treatment in 2020 (38.92 days), like what it was found in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there was no identification of statistical differences for the clinical stage at the lung cancer group, and it is worth mentioning that over 70% of subjects were metastatic at diagnosis [ 29 ]. The results presented by Lou et al [ 30 ] also demonstrated no change in clinical stage at diagnosis for patients with lung cancer besides a shorter time-to-treatment in 2020 (38.92 days), like what it was found in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in vitro experiments might represent a novel pre-clinical example of precision medicine. It is already known that circulating tumor cells and circulating tumor DNA (ctDNA) complement each other on novel approaches regarding tumor heterogeneity, with a potential do predict treatment responses, prognosis 4 , monitoring disease burden 173 , and risk of relapse 174 . In that matter, new pre-clinical in vitro analysis may show that acquired resistance can emerge before the drug exposure occurs, suggesting that some cells are in any case resistant to treatment 4 , yielding an understanding that access tumor's microenvironment in this frontier has the potential to optimize more effective immunology-based precision therapies 4 .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…It is already known that circulating tumor cells and circulating tumor DNA (ctDNA) complement each other on novel approaches regarding tumor heterogeneity, with a potential do predict treatment responses, prognosis 4 , monitoring disease burden 173 , and risk of relapse 174 . In that matter, new pre-clinical in vitro analysis may show that acquired resistance can emerge before the drug exposure occurs, suggesting that some cells are in any case resistant to treatment 4 , yielding an understanding that access tumor's microenvironment in this frontier has the potential to optimize more effective immunology-based precision therapies 4 . In sum, there is hope the optimal use of AI will move precision oncology to a new paradigm with a more efficient journey from biomarker identification and validation, trial design, drug approval and ultimately better and more affordable patient tailored treatments.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…This intertumoral and intratumoral heterogeneity of cancer as a basis for tumour evolution, treatment resistance and subsequent treatment failure, is an area of growing understanding [3]. Recent advances in high-throughput, relatively low-cost sequencing techniques (for example, next generation sequencing (NGS)) have shed light on molecular drivers of cancer, actionable mutations and the continuous process of clonal evolution from selective pressure of cancer therapies [4]. As such, it is widely accepted that personalised or precision medicine will optimise response to cancer therapy and improve quality of life for the patient.…”
Section: Background 1tumour Burden and Heterogeneitymentioning
confidence: 99%